MODERN METHODS OF IMPROVING THE MANAGEMENT SYSTEM IN AGRICULTURE - Gaziyeva Nodira Dilmurot qizi (Web of Journals Publishing, 2025)
Agriculture is a fundamental sector of the global economy, and effective management is crucial for enhancing productivity and sustainability. This article explores modern methods of improving agricultural management systems, focusing on digital technologies, precision agriculture, sustainable farming practices, and management frameworks. The study also presents the results of applying innovative approaches and offers practical recommendations to improve efficiency in agricultural management.
Keywords: diverticulae, transurethral resection, benign prostatic hyperplasia, bladder resection.